The Social - Political Significance of Ruwatan Desa Ritual - Hidayatul Wahidah; Akhmad Jazuli Afandi (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2018)
The Punden of Mbah Sentono is a sacred landscape that is used frequently by people to increase their spirituality. It is recognized as a sacred place to perform rituals such as tahlilan, slametan and ruwatan desa. The main issue I raise in this paper concerns the social-political significance of the rituals. The three main questions are, first, how is ruwatan practiced in the Punden of Mbah Sentono? Second, how have political actors used the ritual in the punden as a political tool in an election? The last, how have people also used the ritual in the punden to counter the political actors’ use the ritual? I will show that the rituals do have social-political significance and argue that both political actors and people in society have mutual relations through the rituals. From this point of view, I state that ritual in the Punden of Mbah Sentono is divided into two time periods, “during election period” and “after election period”. “The ritual during election period” are tahlilan and slametan which are handled by the candidates of the local election to build political support, whereas “the ritual after election” is ruwatan desa which is also used by the winner for negotiation and reconciliation to ease the negative impacts of the competitions during the local election, which affect people. On the other hand, people also use the rituals to ask for financial support from the candidates for holding big ruwatan desa and kirap. In the years before and after the election, ruwatan desa is held as small events. In this research, I analyze the social-political significance of ritual, using a theoretical framework informed by Kertzer. [Punden Mbah Sentono adalah tempat sakral yang sering digunakan sebagai tempat spiritual oleh orang-orang untuk meningkatkan spiritualitas mereka. Punden tersebut diakui sebagai tempat sacral untuk melakukan tahlilan, slametan dan ruwatan desa. Isu utama yang saya angkat didalam tesis ini adalah siknifikansi social-politik pada ritual. Ada tiga pertanyaan utama; yakni, pertama, bagaimana ruwatan desa ritual dipraktekkan di punden Mbah Sentono? kedua, bagaimana actor politik menggunakan ritual didalam punden sebagai alat politik didalam pemilihan? Terakhir, bagaimana masyarakat menggunakan ritual di punden untuk keluar dari actor politik? Saya akan menunjukkan bahwa ritual mempunyai siknifikansi social-politik dan beranggapan bahwa actor politik dan masyarakat mempunyai hubungan timbal balik melalui ritual.]